OUTSOURCING IN CONTIDIONS OF SMEs - THE POTENTIAL FOR COST SAVINGS - Potkany, M.; Stasiak-Betlejewska, R.; Gejdos, M.; Kováč, Róbert (Czestochowa University of Technology, 2016)
Many enterprises face the issue with increasing own overhead cost and take an effort to reduce it, what is a base for using of outsourcing principles. Outsourcing is primarily used as a strategic tool for corporate resources optimizing. Enterprises decide to remove some supporting activities to external units, which can be provided with ensuring a higher quality and lower costs. These decisions result in increasing attention to a core business orientation and costs reduction. The main purpose of the paper is the cost savings quantification, what is supported by the research results focused on the use and the possibilities of outsourcing in Slovakian SMEs. There was proposed a general model for an economic efficiency evaluation for potential use of the outsourcing through determination of expected costs savings as a result of the research study.
OUTSOURCING V PODMÍNKÁCH MSP - POTENCIÁL ÚSPORY NÁKLADŮ
Keywords: outsourcing; cost savings; enterprise; SME; allocation base; outsourcing; úspora nákladů; podnik; MSP; rozvrhová základna